2022
DOI: 10.2147/rmhp.s377249
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Interventions Were Perceived as Effective Against Coronavirus-19 in Nursing Homes in Italy? A Descriptive Qualitative Study

Abstract: Purpose To identify interventions implemented during the first, second and third waves of the Coronavirus disease 2019 (COVID-19) among Italian Nursing Homes (NHs). Patients and Methods A descriptive qualitative design according to COnsolidated criteria for REporting Qualitative (COREQ) guideline. A purposeful sample of five public NHs, located in the north-east of Italy, equipped with from 60 to 151 beds, participated. Six nurse managers, four clinical nurses and one N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…It will also ensure that the policies and plans developed are aligned with the needs of care-home settings. A study by Palese et al (2022) found that nursing home staff had to make decisions and rely on policies that have a limited evidence-base because the policies and guidelines created by regulatory bodies during the pandemic were often generic and not tailored for nursing homes, which meant they had to interpret them on their own and adapt them to local needs, and justify their decisions to regulatory bodies when one guideline or policy was favored over another.…”
Section: Discussionmentioning
confidence: 99%
“…It will also ensure that the policies and plans developed are aligned with the needs of care-home settings. A study by Palese et al (2022) found that nursing home staff had to make decisions and rely on policies that have a limited evidence-base because the policies and guidelines created by regulatory bodies during the pandemic were often generic and not tailored for nursing homes, which meant they had to interpret them on their own and adapt them to local needs, and justify their decisions to regulatory bodies when one guideline or policy was favored over another.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses in our study reported all these issues, identifying that their ability to provide high-quality, personalized care at the micro level was impacted by decisions made at meso and macro levels, over which they had no or little power, thus feeling disempowered by the process. Further, care-home RNs found themselves making decisions and relying on guidance that had a limited evidence-base (Palese et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses in our study reported all these issues, identifying that their ability to provide high‐quality, personalized care at the micro level was impacted by decisions made at meso and macro levels, over which they had no or little power, thus feeling disempowered by the process. Further, care‐home RNs found themselves making decisions and relying on guidance that had a limited evidence‐base (Palese et al, 2022). Regulatory bodies created policies and guidelines, often generic rather than care‐home specific, and not always aligned with each other, so care‐home staff had to interpret and apply to local need, and justify decision‐making to regulatory bodies when one guideline or policy was favored over another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations